Spies in uniform British military and naval intelligence on the eve of the First World War - Seligmann, Matthew S., 1967- (Oxford University Press, 2006)
Today many historians argue that in 1914 Germany posed no threat to British national security and that a million British citizens died needlessly for a misguided cause. This book disputes the suggestion that the British government either got its facts wrong or 'invented' the German threat.